Investigating characters in the first three volumes of the novel “Fire without Smoke” - NAMI SHARIF ABAD, R.; ASHRAFZADEH, R.; MEHRBAN, J. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Familiarity with various branches of literature, especially fictional literature, has been an appropriate setting for cultural and social change. Since fictional literature and characterization are one of the most interesting and important areas in the field of fictional research, and basically a story without character is not conceivable, this article examines personality in the first three volumes of the novel Smoke-free Fire Ibrahimi and such things as personal descriptions (Direct and indirect), simple and comprehensive, the social class, the motive of the characters in our actions. In general, Ibrahim can be highly successful in characterizing his prose. RESUMEN La familiaridad con varias ramas de la literatura, especialmente la literatura de ficción, ha sido un escenario apropiado para el cambio cultural y social. Dado que la literatura y la caracterización ficticias son una de las áreas más interesantes e importantes en el campo de la investigación ficticia, y básicamente una historia sin personajes no es concebible, este artículo examina la personalidad en los primeros tres volúmenes de la novela Fuego sin Humo, Ibrahimi y tales cosas como descripciones personales, simples y completas, la clase social, el motivo de los personajes en nuestras acciones. En general, Ibrahim puede tener mucho éxito en caracterizar su prosa.